ChemInform Abstract: Sodium Iodide‐Catalyzed Direct α‐Alkoxylation of Ketones with Alcohols via Oxidation of α‐Iodo Ketone Intermediates. Issue 25 (5th June 2015) - Zhu, Cuiju; Zhang, Yuanfei; Zhao, Huaiqing; Huang, Shijun; Zhang, Min; Su, Weiping
Abstract: α‐Iodo ketones are the key reaction intermediates which are converted into α‐alkoxylated ketones via further oxidation to hypervalent iodine species rather than nucleophilic substitution.